2015
DOI: 10.3389/fpls.2015.01104
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomic Response of Arabidopsis thaliana to Cadmium Sulfide Quantum Dots, and Its Correlation with the Transcriptomic Response

Abstract: A fuller understanding of the interaction between plants and engineered nanomaterials is of topical relevance because the latter are beginning to find applications in agriculture and the food industry. There is a growing need to establish objective safety criteria for their use. The recognition of two independent Arabidopsis thaliana mutants displaying a greater level of tolerance than the wild type plant to exposure to cadmium sulfide quantum dots (CdS QDs) has offered the opportunity to characterize the tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 35 publications
4
30
1
Order By: Relevance
“…4C). Similar to previous parallel analysis (Bai et al, 2015; Marmiroli et al, 2015), much less overlap was observed between DEP and DEG, DAS and DASP as well as DEP and DASDP (Fig. 4A-C).…”
Section: Resultssupporting
confidence: 88%
“…4C). Similar to previous parallel analysis (Bai et al, 2015; Marmiroli et al, 2015), much less overlap was observed between DEP and DEG, DAS and DASP as well as DEP and DASDP (Fig. 4A-C).…”
Section: Resultssupporting
confidence: 88%
“…A subset of conserved Fe-responsive genes and some common metabolic pathways have been revealed by transcriptome and proteome across a range of plant species. It has been clear that the concordance between the abundance of mRNA and their related proteins is not strong correlated (Lan et al, 2012a, 2013a; Li et al, 2013; Marmiroli et al, 2015; Dong et al, 2016). The integration of transcriptome and proteome is mandatory for generating a complete inventory of the components that are crucial for Fe homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-throughput transcriptomic studies have provided a global view of gene expression changes, surveys at the transcript level often could not directly estimate the abundance and functions of the encoded proteins, the ultimate players of biological function, due to alternative RNA splicing and complex posttranslational modifications such as phosphorylation, glycosylation, methylation, ubiquitination, and so on (Lan et al, 2012a, 2013a; Marmiroli et al, 2015; Dong et al, 2016). These various modifications thus change protein localization, stability, interactions, and functions, leading to much more complex of proteomics than that of transcriptomics.…”
Section: Proteomes Of Fe Deficiecny In Plantsmentioning
confidence: 99%
“…For nanotoxicological investigation, the microarray technology has been applied to detect changes in gene expression in human cells (Li et al, 2014), zebrafish embryos (Van Aerle et al, 2013), and bacteria (Escherichia coli) (Cui et al, 2012). For plants, microarray has been applied to detect changes in gene expression in plants exposed to and CdS quantum dots (QDs) (Marmiroli et al, 2014(Marmiroli et al, , 2015 and Ag NPs (Kaveh et al, 2013). Marmiroli et al (2014) reported that sensitivity of Arabidopsis thaliana to CdS QDs was not due to the released Cd 2þ ions according to differential responses of Arabidopsis genes.…”
Section: Introductionmentioning
confidence: 99%